2018
DOI: 10.11118/actaun201866020619
|View full text |Cite
|
Sign up to set email alerts
|

Several Methods of Estrus Detection in Cattle Dams: A Review

Abstract: The oestrus is defined as a complex of physiological signs and changes of behavior occurring immediately before the ovulation. It is the period of sexual receptivity of the cow and this period characterized by, typical cow behaviour which is standing when mounted by a bull or companion cow. Cow indicates this willingness by a slight arching of the back and immobility when approached. The bovine estrus cycle averages 20 days in heifers and 21 days in cows, but the fluctuations in the cycle length is laying betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…The sensing system allows radio communication to detect estrus even at greater distances (up to 50 meters) from the installed radio antenna. According to the available data, this device shows up to 90% of heat detection reliability based on the evaluation of increased locomotion activity (Mičiaková et al, 2018). Roelofs et al (2005a) and Arney et al (1994) confirmed by the use of monitoring devices, that the locomotion activity of dairy cows increases during estrus.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The sensing system allows radio communication to detect estrus even at greater distances (up to 50 meters) from the installed radio antenna. According to the available data, this device shows up to 90% of heat detection reliability based on the evaluation of increased locomotion activity (Mičiaková et al, 2018). Roelofs et al (2005a) and Arney et al (1994) confirmed by the use of monitoring devices, that the locomotion activity of dairy cows increases during estrus.…”
Section: Introductionmentioning
confidence: 93%
“…The estrus is defined as a complex of physiological signs and changes of behavior occurring immediately before the ovulation (Mičiaková et al, 2018). Behavior around estrus is according to Forde et al (2011) induced predominantly by the action of estrogens (17β estradiol), which transmit stimuli to the brain from pre-ovulation follicles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the detection of the first estrus symptoms is difficult to ascertain accurately. For this reason, instruments to detect estrus period onset in cows have been developed and tested in previous studies [8,9]. The use of an estrus detector in the field…”
Section: Introductionmentioning
confidence: 99%
“…can help breeders detect the first appearance of estrus, which can lead to an increase in conception rate from AI [3,6]. Recently, there are several methods to predict the first appearance of estrus, such as observing body and vaginal temperature, rumination time, lying behavior, mounting and standing-to-be-mounted behavior, and physical activity [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This can be put into context with length of individual feed particles, when longer particles require longer rumination time (Nørgaard et al, 2011). Another factor that affects the length of rumination is lying time (Schirmann et al, 2012) and heat time (Reith and Hoy, 2012;Mičiaková et al, 2018). According to de Ondarza et al (2017) changes in rumination time may indicate health problem earlier than clinical changes occur and before decrease of milk production.…”
Section: Introductionmentioning
confidence: 99%